Konservasi Ekosistem Mangrove melalui Pengembangan Ekowisata Berbasis Masyarakat di Kota Batam - Ahdarrijal, Yujitia; Badrudin, Muhammad; Batubara, Ebenezer (Dialektika Publik, 2025)
This research explores the conservation of mangrove ecosystems through the development of community-based ecotourism in Batam City, Indonesia. Mangroves play a vital role in maintaining coastal resilience, supporting biodiversity, and mitigating climate change, yet in Batam, they face significant pressures from rapid urbanization, land conversion, and industrial expansion. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis involving local communities, government representatives, ecotourism managers, and non-governmental organizations. The findings reveal that community-based ecotourism initiatives, such as those in Kampung Tua Bakau Serip, contribute not only to environmental conservation but also to improving local livelihoods and strengthening social cohesion. However, challenges remain, including limited infrastructure, inconsistent policy implementation, and varying levels of community participation. The study underscores the importance of multi-stakeholder collaboration, integrating conservation efforts with local economic development, and aligning ecotourism practices with the principles of sustainable development. By emphasizing community empowerment and adaptive governance, this research contributes to the broader discourse on sustainable coastal management and offers policy recommendations to strengthen mangrove conservation in Batam and similar urban coastal areas.